Description of Standardized Planes and Angles for Percutaneous Supra-acetabular Screw Placement - Rüwald, Julian; Ploeger, Milena Maria; Hischebeth, Gunnar T; Tüllmann, Mareike; Roos, Jonas; Gathen, Martin; Kabir, Koroush (The Journal of Hip Surgery, 2024)
Background Percutaneous screw fixation for pelvic fractures has become a minimally invasive alternative to an open operation. The complex anatomy of the pelvis renders this procedure challenging. The objective of this study was to assess standardized angles and dimensions of safety zones within a 3 D computed tomography model for optimal supra-acetabular screw placement.Methods Computed tomography scans of 107 patients that suffered major trauma without showing any bone injury of the pelvis were collected. Using a software-based analysis, raw computed tomography data were transformed into 3 D models to set standardized landmarks and determine the possible insertion corridor.Results Screws not exceeding a length of 97 mm in females and 106.4 mm in males were, in 95% of the evaluated cases, insertable without cortical bone penetration. The safety zone was 6.6 mm for females and 7.9 mm for males. Screws not exceeding these diameters were safely insertable in 95% of the cases. For the midsagittal plane, the angle was 36.4 ± 5.1 on the left and 34.7 ± 2.9 on the right (p = 0.008). For the anterior pelvic plane, the angle was 31.3 ± 4.5° on the left and 34.0 ± 4.8° on the right (p = 0.008).Conclusions Percutaneous fixation using supra-acetabular screws is a promising method to treat simple supra-acetabular fractures. These results may improve its safe utilization and could facilitate its broader clinical application.
Keywords: pelvis; pelvic ring fractures; screw insertion angle; supraacetabular screw